Hyde & seek - Green, Simon R., 1955- (Jekyll & Hyde Inc., 2024)
"Whatever happened to all the old monsters? The vampires, the werewolves, the ghouls . . . Daniel & Tina Hyde wiped them out, to make the world a safer place. But nature abhors a vacuum, supernature even more . . . Something's got to fill the gap left by all those monster clans. The question now is, what happened to all the old aliens? The Martians, the Bug-Eyed Monsters, the Reptiloids and the Greys? They're coming out of the shadows with a vengeance, and Daniel and Tina Hyde are about to discover there are much worse things than monsters. Fortunately, Hydes love a good fight. Daniel and Tina are in for the fight of their lives, with the whole world at stake"--